Lhermitte-Duclos Disease with Cervical Arteriovenous Fistula - Almubarak, Abdulaziz Oqalaa; Haq, Anwar Ul; Alzahrani, Ibrahim; Shail, Essam Al (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2019)
Lhermitte-Duclos disease is a rare condition with less than 250 cases reported in the literature. It was considered a neoplastic or hamartomatous growth in the cerebellum. It commonly presents with symptoms of high intracranial pressure or obstructive hydrocephalus. Surgical resection is often curative. The lesion is associated with PTEN gene mutation, and it is considered to be one of the diagnostic criteria of Cowden's syndrome. Vascular tumors are reported in this syndrome, including glioblastomas and meningiomas. Furthermore, central nervous system vascular lesions were also reported in Lhermitte-Duclos disease, such as deep venous anomalies and brain arteriovenous fistulas. A report of an asymptomatic spinal cervical AVF in a patient with Lhermitte-Duclos disease was published in 2006. We present the second case of Lhermitte-Duclos disease associated with an asymptomatic spinal cervical AVF in a 17-year-old young woman with literature review of central nervous system vascular lesions in Lhermitte-Duclos disease.
Keywords: Lhermitte-Duclos; arteriovenous fistula; PTEN; Cowden's syndrome; vascular malformation